2012
DOI: 10.1590/s1519-69842012000500006
|View full text |Cite
|
Sign up to set email alerts
|

Faunistic analysis of the species of Anastrepha Schiner (Diptera: Tephritidae) in three municipalities of the state of Roraima, Brazil

Abstract: The purpose of this work was to describe the population patterns of Anastrepha in three municipalities of the state of Roraima, Brazil, via faunistic analysis. Weekly collections were performed from January through December 2008, using McPhail traps containing 5% hydrolysed protein, in domestic orchards in the municipalities of Boa Vista, Bonfim and Pacaraima. We captured 301 females of Anastrepha in Boa Vista, 212 in Bonfim, and 167 in Pacaraima. Boa Vista presented the highest species richness (S = 10) and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
2
2
0
2
Order By: Relevance
“…Anastrepha fraterculus was the most frequent, dominant and constant species, being present in all localities, followed by A. obliqua, A. sororcula and C. capitata, which were frequent, dominant and constant in certain municipalities studied (Table 1), corroborating several studies involving the faunistic analysis of tephritids, which found the occurrence of two to three dominant species in different regions of Brazil (HUSCH et al, 2012;MARSARO JÚNIOR et al, 2012;ARAUJO et al, 2013).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Anastrepha fraterculus was the most frequent, dominant and constant species, being present in all localities, followed by A. obliqua, A. sororcula and C. capitata, which were frequent, dominant and constant in certain municipalities studied (Table 1), corroborating several studies involving the faunistic analysis of tephritids, which found the occurrence of two to three dominant species in different regions of Brazil (HUSCH et al, 2012;MARSARO JÚNIOR et al, 2012;ARAUJO et al, 2013).…”
Section: Resultssupporting
confidence: 84%
“…Information on the faunistic analysis of tephritids is crucial for understanding the bioecology of these insects in different areas (MARSARO JÚNIOR et al, 2012). Therefore, several studies have been conducted around the world using food traps in order to know the diversity, monitor and/or control tephritids (ORDANO et al, 2013;TAIRA et al, 2013;ALI et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The data analyzed here were obtained mainly from papaya orchards, although probably with some influence from urban and Atlantic forest remnant areas. The maximum richness found here is coherent with fruit fly surveys in tropical areas, which generally do not find richness levels higher than those estimated in this study (Almeida et al, 2019;Marsaro Júnior et al, 2012). The abundance of flies also changed during the study period.…”
Section: Discussionsupporting
confidence: 89%
“…Lepidopteran families were grouped in abundance classes according to CIs (Thomazini and Thomazini, 2002;Silva et al, 2011;Marsaro Júnior et al, 2012): ma= very abundant (number of individuals greater than the upper limit of the CI at 1%), abundant (a), common (c), dispersed (d) and rare (r), respectively, with number of individuals between the upper limits of the CI at 5 and 1%, within the CI at 5%, between the lower limits of the CI at 5 and 1%, and under the lower limit of the CI at 1%.…”
Section: Data Collection and Statisticsmentioning
confidence: 99%